2003
DOI: 10.1213/01.ane.0000064206.51296.1d
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia in Children Undergoing Myringotomy and Placement Equalization Tubes in Ambulatory Surgery

Abstract: We compared four different analgesics in the management of pain after placement of pressure equalization tubes during myringotomy in children and demonstrated that ketorolac or butorphanol provided superior analgesia when compared with acetaminophen with codeine or plain acetaminophen. Children who received ketorolac versus butorphanol had less vomiting in the 24 h after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Paracetamol also has little antiplatelet activity and does not affect bleeding time, unlike NSAIDs [7]. Although enteral formulations of paracetamol are the most commonly used analgesics for management of pain in children, their analgesic efficacy is weak after ENT surgery [8,9]. An intravenous (IV) formulation of paracetamol recently has become available, and it achieves target plasma concentration more rapidly with reduced variability compared with the rectal and oral formulations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Paracetamol also has little antiplatelet activity and does not affect bleeding time, unlike NSAIDs [7]. Although enteral formulations of paracetamol are the most commonly used analgesics for management of pain in children, their analgesic efficacy is weak after ENT surgery [8,9]. An intravenous (IV) formulation of paracetamol recently has become available, and it achieves target plasma concentration more rapidly with reduced variability compared with the rectal and oral formulations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A small number of randomized, controlled trials in children have also shown effective analgesia, with a reduction in morphine requirements leading to reduced postoperative vomiting compared with an opioid-based analgesic. 110 However, bleeding time may be increased, 111 and some reports 112 show an increase in postoperative clinical bleeding, although there are no randomized, controlled trials that have included neonates. A case series of infants younger than 6 months after abdominal surgery suggested a reduction in morphine requirements when ketorolac was used.…”
Section: Reducing Pain From Surgerymentioning
confidence: 99%
“…One commonly used option, the administration of rectal acetaminophen, has been shown to provide insufficient analgesia when used alone [13]. In many centers, IN fentanyl remains a commonly used analgesic although there are questions regarding its efficacy and investigations continue in the hopes of finding a better alternative.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tympanic membrane is quite sensitive and given that intravenous access is not available, an alternative route of drug delivery for postoperative analgesia is needed. In many cases, acetaminophen is administered per rectum; however, this alone is generally not sufficient to provide effective analgesia [13]. Other suggested regimens for the provision of postoperative analgesia have included oral acetaminophen–codeine, intramuscular (IM) ketorolac and intranasal (IN) butorphanol; although perhaps the most commonly employed analgesic method is IN fentanyl [47].…”
Section: Introductionmentioning
confidence: 99%